Generation of dissipative soliton in er-doped all-fiber oscillator based on a femtosecond laser inscribed 45° tilted fiber grating - Huang, Zinan; Huang, Qianqian; Theodosiou, Antreas; Kalli, Kyriacos; Mou, Chengbo (My University, 2020)
A dissipative soliton mode-locked all-fiber laser using a femtosecond laser inscribed 45° tilted fiber grating (TFG) is demonstrated. Our work indicates that femtosecond laser inscribed 45° TFGs have great application potential in high-energy ultrafast lasers.
Keywords: Fiber lasers; All-fiber lasers; Femtosecond lasers; Fiber grating